Fenomena Buzzer Dalam Perspektif Komunikasi Politik Di Media Sosial Jelang Pemilu 2024 - Wulandari, Charisma Dina (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Elections are an important moment in the democratic life of a country, where the people have the opportunity to elect its leader and deputy. In an increasingly advanced digital age, social media has become a significant platform in influencing public opinion and shaping political narratives. The rapid development of technology must also be accompanied by the character of social media users, so that the progress of the times will be in harmony. In order to receive and disseminate information through technology based on real facts. This study aims to provide a description of the phenomenon of spreading hoax news, namely buzzers ahead of the 2024 election from social media, as well as how to respond to the hoax news. This research method uses qualitative descriptive, where this method uses qualitative approach research methods in order to describe and see data and facts about hoaxes and how to overcome them. The result is if this cheap and easy technological advancement becomes a determining factor when accessing information and social media connoisseurs become smarter when using information, namely in understanding media literacy which is often considered as real truth news. The role of the government in controlling its dissemination is the existence of the right legal policy that has been regulated and listed in the ITE Law. The promotion procedure also reflects the homogenization (similarity) of characteristics between account holders and followers. Social unrest is caused by the rise of fake news in Indonesia. Social media users can respond to this by becoming social media users who are more wise and shrewd, and careful in disseminating information. Keywords: Buzzer, Hoax, Social Media; UU ITE.